The PC goes ready-to-wear. - Ditlea, S.
Concentrating the computational power of a multimedia desktop or laptop computer into a central processing unit only slightly larger than a hand-held organizer, wearable PCs are finding plenty of users in the commercial world. What wearable computers have to offer is job-critical information to people whose hands must be free for other work. Assembly line workers, for example, can access a database and look at drawings of what's being worked on and see step-by-step instructions for putting it together. These are shown on a small color display that hangs before a worker's eye, supported there by a head-mounted boom. The rest of the system-its central processing unit (CPU), which includes a microprocessor, RAM, and hard drive-is worn in a belt around the waist. The display is a small liquid-crystal chip, whose image is picked up by a silvered mirror, or transmitted through a prism, and reflected or redirected into the user's eye. The display is held at the end of a toothbrush-sized boom, supported by a headboard, say, or by a larger eye-covering mirror or prism arrangement. Thanks to magnifying optics and despite the closeness of the image to the eye, the viewer has the illusion of reading a normal-sized desktop screen at the usual arm's length viewing distance. Commands are either keyed into a small keyboard worn on the wrist or spoken into a microphone. A video camera is an option, and the computers have standard I/O ports for adding peripherals. In addition, the machines can handle off-the-shelf applications, such as database management and word processing, written for Windows or Linux operating systems. Just what is displayed varies, of course, depending upon the imagination of the system designer and the application. The computers are not cheap, ranging from US 5000 to 10000 dollars. They may be worth it, though, for what they can add to a person's job effectiveness
Keywords: I/O ports; Central processing unit; Database management; Keyboard; Microphone; Video camera; Wearable PCs